2019
DOI: 10.1371/journal.pone.0213585
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intravenous infiltration using impedance parameters in patients in a long-term care hospital

Abstract: This study was aimed to evaluate the changes of impedance parameters of patients who were admitted to a long-term care hospital by measuring bioelectrical impedance. The subjects were 18 patients who had infusion therapy through peripheral intravenous (IV) catheters and had at least an infiltration. The impedance parameters were measured with a multi-channel impedance measuring instrument (Vector Impedance Meter) twice; at starting IV infusion after catheter insertion and infiltration detected. As results, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Five of the technologies focused solely on signal processing mechanisms 14,15,18,21,23. Signal processors are composed of 3 general components: a source, a medium, and a receiver.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Five of the technologies focused solely on signal processing mechanisms 14,15,18,21,23. Signal processors are composed of 3 general components: a source, a medium, and a receiver.…”
Section: Discussionmentioning
confidence: 99%
“…Saade and Brennan14 collected radiofrequency tissue data from 25 adults and detected all stages of early leakage/infiltration. On 18 adult patients, Jeong et al23 found that bioimpedance was an effective method of infiltration detection, as the impedance parameters of resistance, reactance, and capacitance showed significant differences before and after infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations